2015
DOI: 10.1049/iet-map.2014.0689
|View full text |Cite
|
Sign up to set email alerts
|

Wideband circularly polarised array antenna with flat‐top beam pattern

Abstract: A wideband circularly polarised array antenna consisting of 10-element bowtie dipole antenna and feed network is presented. A narrow patch connecting the pair of bowtie dipoles as an entity is employed to achieve high gain. To obtain wideband and flat-top beam of radiation patterns, amplitude and phase distribution along the feed are optimised by application of the Self-adaptive Differential Evolution algorithm. Particularly, the feed network with broadband phase shift performance is designed to satisfy bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This article investigates the SBPS problem by optimizing the array weight. Two typical SBPs, including the flat-top beam pattern [10][11][12] and the cosecant square beam pattern [13][14][15] would be discussed. These two types of patterns are commonly used in 4G communication and satellite communication.…”
Section: Introductionmentioning
confidence: 99%
“…This article investigates the SBPS problem by optimizing the array weight. Two typical SBPs, including the flat-top beam pattern [10][11][12] and the cosecant square beam pattern [13][14][15] would be discussed. These two types of patterns are commonly used in 4G communication and satellite communication.…”
Section: Introductionmentioning
confidence: 99%
“…A leaky‐wave antenna working at 10 GHz is optimised to shape the flat‐top pattern, the angular range is ±8.6° with a ripple of 1 dB, and the operating band is 7% [6]. In [7], a circular polarisation array antenna with flat‐top beam operating from 1.1 to 1.6 GHz covers ±12° in the elevation plane, the ripple is better than 0.92 dB.…”
Section: Introductionmentioning
confidence: 99%
“…In modern communication and radar systems, a differential phase shifter has been extensively integrated into phased-array antennas [1], beamforming networks [2] to digitally control the beam direction and into antenna feeding networks [3] to realise the circular polarisation. Many research studies have been reported on the development of a variety of differential phase shifters [4][5][6][7][8][9][10][11][12][13][14][15] with the wideband property, small phase deviation, low amplitude imbalance and reasonable process cost.…”
Section: Introductionmentioning
confidence: 99%